2021
DOI: 10.1002/pros.24231
|View full text |Cite
|
Sign up to set email alerts
|

The role of histopathological and biochemical parameters for predicting metastatic disease on 68Ga‐PSMA‐11 PET in prostate cancer

Abstract: Background: The aim of this study was to evaluate the role of histopathological and biochemical parameters in the prediction of the presence and number of PSMA positive lesions consistent with the metastatic spread of prostate cancer on 68 Ga-PSMA PET images.Methods: Biochemical, histopathological and imaging data of 302 prostate cancer patients who underwent 68 Ga-PSMA-11 PET/CT or PET/MR imaging for primary staging were retrospectively analyzed. Patients were divided into two groups as "PET positive" and "PE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…Along with the radiologic tumor stage, the proportion of positive prostate biopsies was associated with the presence of metastatic disease on PSMA PET/CT in our study. This is equally the case for the proportion of ISUP GG3 in prostate biopsies and in line with preexisting literature (27). The presence of these associations may be explained by potential improper grading at the time of biopsy.…”
Section: Discussionsupporting
confidence: 90%
“…Along with the radiologic tumor stage, the proportion of positive prostate biopsies was associated with the presence of metastatic disease on PSMA PET/CT in our study. This is equally the case for the proportion of ISUP GG3 in prostate biopsies and in line with preexisting literature (27). The presence of these associations may be explained by potential improper grading at the time of biopsy.…”
Section: Discussionsupporting
confidence: 90%
“…In a study by Bluemel et al, Ga-68 PSMA PET/CT positivity showed a significant correlation with PSA level and PSA increase rate in recurring prostate cancer patients with negative F-18 Choline PET/CT [20]. Similarly, Aydos et al showed that total PSA and ISUP group were associated with metastatic spread of prostate cancer on Ga-68 PSMA PET images [21]. However, there is no consensus on the exact level of PSA for referring patients to the PET scan [22].…”
Section: Discussionmentioning
confidence: 91%
“…Similarly, Aydos et al . showed that total PSA and ISUP group were associated with metastatic spread of prostate cancer on Ga-68 PSMA PET images [21]. However, there is no consensus on the exact level of PSA for referring patients to the PET scan [22].…”
Section: Discussionmentioning
confidence: 99%
“…O'Rourke et al 29 further found that a SUVmax > 3.0 could be similarly used to aid in the diagnosis of supraclavicular lymph nodes in esophageal cancer patients. Given that we employed a PSMA‐specific tracer in the present study, which has a promising comparative noise ratio and superior specificity for prostate cancer cells, 31 this may explain the observed diagnostic value of a lower SUVmax cutoff value in the context of LNM detection in PCa patients.…”
Section: Discussionmentioning
confidence: 98%